POLYMER ADDITIVE EFFECT ON THE STRUCTURAL AND MECHANICAL PROPERTIES OF THE ORGANIC PART OF OIL BITUMINOUS ROCK - Narmanova Roza Abdibekovna; Bishimbayev Valikhan Kozykeevich; Tapalova Anipa Seidalievna; Appazov Nurbol Orynbassaruly (Academic Scientific Journal of Chemistry, 2020)
The article presents the results of gas chromatographic analysis method of the organic part of oil bituminous rock and the results from the analysis of the molecular weight distribution of atactic polypropylene carried out using reverse gel-permeation chromatography. The research results of the structural and mechanical properties of the bitumen part of oil bituminous rock (OBR) of the Iman-Kara deposit, atactic polypropylene (APP) and compositions based on them, carried out on the instrument Reotest 2.1, are also presented herein. It has been determined that the organic part of OBR of the Iman-Kara deposit mainly consists of oxygencontaining organic compounds with additions of heteroatomic structures (sulfur, haloids and nitrogen) with a weight fraction of 53.97%. According to the chromatogram of the molecularly-mass distributed atactic polypropylene, it is found that the average time of fraction maximum yield is 11.4 minutes, the corresponding value of logarithm of the average molecular weight Lg(M) equals to 5.5. Accordingly, the average molecular weight of fraction M is 400. The change patterns of the rheological properties of the organic part of OBR, atactic polypropylene and compositions based on them are described. It has been established that the addition of APP to the organic part of OBR creates a disperse system in which the particles of a polymer additive that are swollen due to oily components are dispersed in the bitumen medium. At the same time, mechanical properties such as elasticity and heat resistance of the organic part of oil bituminous rock are improved. These properties can be shown only with the optimum quantity of APP, when their concentration is such that they form an uninterrupted net structure. The influence patterns of APP on the structure of the organic part of OBR defined in the process of experiments can also be used in further experiments during development of various types of waterproofing materials and coatings.